THE EFFECT OF CHINA’S TRAVEL PURPOSES ON HUNGARY’S INBOUND TOURISM - Mahlatse MABEBA; Xinxin XU (Eastern European Journal of Regional Studies, 2023)
This paper conduct an empirical research and investigate the effect of China’s travel purposes on Hungary’s inbound tourism during a period of uncertainty. The study takes into account the influence of the Covid-19 and Ukraine-Russia war on inbound tourism. The short-run monthly sample from January 2018 to July 2022 has been utilzed to capture the uncertain period. A Poisson Regression Model has been applied to calculate the efficacy of China’s travel purposes on Hungary’s inbound tourism. This study finds that China’s leisure and business trips have positive and significant effect on Hungary’s inbound tourism. China’s business trips has a large contribution to Hungary’s inbound tourism than leisure trips. During the uncertain period, the Covid-19 and Ukraine-Russia war had a negative and significant effect on arrivals of tourists to Hungary. Inbound tourism from China to Hungary had contributed positively to the economic performance of Hungary’s tourism sector.